Effect of feeding and management on growth andsurvival of Wallago attu (Scheneider) larvaeduring hatchery rearing - Sahoo, S K; Giri, S S; Sahu, A K; Gupta, S D (Indian Journal of Fisheries, 2014)
Experiments on larval rearing of large freshwater catfish, Wallago attu wereconducted by feeding plankton alone or in combination with minced fish, molluscor goat liver. The performance of larvae fed on different feeds during non-segregation and segregation was analysed with respect to survival. The larvaefed on goat liver along with plankton attained significantly higher (P